A novel HPLC-DAD method for simultaneous determination of febuxostat and diclofenac in biological samples: pharmacokinetic outcomes. (26th November 2018) - El-Yazbi, Fawzy A; Amin, Omayma A; El-Kimary, Eman I; Khamis, Essam F; Younis, Sameh E; Elkhatib, Mohammed AW; El-Yazbi, Ahmed F
Aim: To develop a simple HPLC-DAD method for simultaneous determination of febuxostat (FEB) and diclofenac (DIC) in biological samples to assess pharmacokinetic outcomes of their coadministration.Methodology & results: Sample preparation was performed by liquid–liquid extraction. Drugs analysis was done on C18 column using methanol-formic acid pH 2.1 (76:24, v/v) as mobile phase and time-programmed UV detection. Lower limits of quantitation for FEB and DIC were 10 and 20 ng/ml, respectively. Baseline pharmacokinetics were similar to published data on either drug alone. Coadministration led to more than twofold increase in FEB Cmax and AUC together with a reduced hepatic uptake in rats.Conclusion: DIC interfered with initial distribution and terminal clearance of FEB potentially due to reduced FEB hepatic uptake.